Fidelización del cliente del comercial Ricardito Jr. en la parroquia San Juan periodo 2021. - Soriano Arana, Cristina Isabel Mercedes (2022)
This study is called "Customer loyalty of the Ricardito Jr. commercial in the San Juan parish" and is developed with the objective of analyzing the loyalty strategies that are applied in the Ricardito Jr. commercial through the specification of the activities that are carried out. They develop on a daily basis for sale, for its effect it is necessary to consider the line of investigations Financial, administrative, tax, audit and control, in addition to the marketing and commercialization subline. The methods that are applied are descriptive because they specify the processes that will be developed to attract and retain customers, on the other hand, the analytical method synthesizes and classifies the relevant information in order to determine the existing problems and the bibliographic method contributes in the compilation of information based on the criteria of different authors. The techniques that agreed on the acquisition of information are the interview and the surveys, with the help of the interview questionnaire instruments applied to the owner-manager of the Ricardito Jr. commercial and the survey form carried out on 14 employees of the company. It was obtained as a result that the loyalty strategies that are applied are: offer of a personalized service and in direct contact with the clients, not making promises that are impossible to fulfill, design of a loyalty program depending on the type of clients, management of complaints suggestions and claims in addition to the use of social networks to build customer loyalty through online advertising.